Simulation work on blood glucose control for type1 diabetes using Modified Hovorka Equations: article - Zawawi, Nurafiqah; Md. Som, Ayub; Mohd Yusof, Nur Farhana
The failure of pancreas can cause uncontrolled blood glucose level in the body. This research focuses on type 1 diabetes patients which depend on external insulin injection. In previous studies, Hovorka models are used as the mathematical models in the artificial pancreas controller. However, the models showed lacking of interaction on glucose-insulin dynamic system. The improvement of Hovorka models had been done, but no work was carried out to simulate the proposed equations. The objectives of this research are to simulate the Modified Hovorka equations using Matlab and to compare the simulation results between the reference and modified one. This study shows different interaction of all the variables and parameters on glucose-insulin dynamic system between both cases. The lower administered amount of insulin (16.7mU/min and 20mU/min) can regulate the blood glucose level at normoglycemia condition.